Los Food as a transmitter of viruses: A review - Espinoza-Tellez, Teofilo (2022)
Viruses have been present throughout human history, causing diseases due to infections and food poisoning; they have caused frequent public health problems worldwide. These illnesses are usually mild, moderate, or severe in nature. The personal hygiene of food handlers and processing processes should be checked periodically. Virus detection protocols and safety measures should be continually reviewed as viruses change their mode of infection. The objective of this review was to discuss the possible routes of virus transmission to humans through food. Important topics have been reviewed such as: definition of food viruses, presence, and types of viruses in food, enteric viruses, zoonotic viruses, water as a means of transmission, risks of infection, other non-conventional foods as potential transmitters of viruses and food safety, in addition to current and future challenges, research work on viruses more resistant to heat treatments in food should be sought. Also, future work on survival time of active viruses on food surfaces. In addition, studies that determine the mechanisms of virus mutation in relation to the conditions of food handling and processing.